Conjugate observations of flow diversion in the magnetotail and auroral arc extension in the ionosphere. Issue 8 (19th August 2013) - Yao, Z. H.; Angelopoulos, V.; Pu, Z. Y.; Fu, S. Y.; Kubyshkina, M.; Liu, J.; Chu, X. N.; Nishimura, T.; Cao, X.; Du, A. M.; Yue, C.; Shi, Q. Q.; et al.
Abstract: [1] We present a case study of a plasma flow diversion event in the inner magnetosphere to illustrate the effects of near‐Earth pressure evolution, field‐aligned current (FAC) generation, and associated auroral evolution during conjugate observations from THEMIS satellites and All‐Sky Imagers (ASIs) on 29 January 2008. At ~0831 UT, an earthward flow at THC, at X ~ 18 Re, was observed which was likely to be associated with an auroral streamer observed at the ASI station FSMI. Near‐Earth satellites THD and THE, separated in the Y‐direction by ~1 Re, and magnetically mapping onto the preexisting aurora arc, also observed the earthward flow but with a small Alfvén transit time of ~20 s between the magnetotail and the ionosphere. As the earthward flow arrived at THD and THE, the aurora arc near the footprints of THD and THE brightened. A duskward pressure gradient developed between THD and THE in the equatorial magnetotail, corresponding to an upward FAC and consistent with the auroral brightening. At ~0834 UT, an eastward diversion of the flow was observed first at THE and later at THD, further to the East. At the head of that flow, pressure variations, coherent between THE and THD, were observed to propagate Eastward at ~400 km/s, consistent with an eastward auroral expansion near the footprints of THE and THD. Concurrent perturbations of the B y component of the magnetic field signify eastward motion of a FAC pair at the two spacecraft locations. We interpret the pressure variations as the generator of the observed FAC that feeds the arc and its eastward expansion. Key Points: The auroral arc extension is clearly related to the flow diversion. The upward FAC is generated by the compression wave. The angle of the oblique compressional wave is presented.